Resort Spa: Peluang Bisnis Perawatan Tubuh di Desa Wisata Gunung Salak, Tabanan, Bali - Ni Nyoman Suci Arthini; Ida Ayu Sri Puspa Adi; Ni Ketut Sekarti (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
The purpose of this article is to review the implementation of community service activities carried out in Gunung Salak Tourism Village, Bali with the topic: Resort Spa: Body Care Business Opportunities in Tourism Villages. The activity was carried out for one day on April 7, 2020. The place for the implementation of the activities was in Banjar Kemetug with 30 participants who were homestay managers, youth and young women in Gunung Salak Village, PKK mothers and housewives. The training method is carried out using demonstration methods, practice, working in groups and asking questions. The results of this activity increase and add insight and knowledge of the community in Gunung Salak Tourism Village in utilizing the potential that exists in their village. This activity also empowers local geniuses by providing opportunities for the community to be able to work and innovate to build small businesses in the Spa sector. The skills provided range from simple/simple treatments to complete treatments which are currently the needs of the general public, not only for tourists, but also for urban communities.